Pendampingan Penyusunan Laporan Keuangan Pada UMKM Klasika Photography Yogyakarta - Erdi, Tio Waskito (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The purpose of community service activities is to provide an understanding of the process of preparing financial reports according to the standards applicable to UMKM Klasika Photography. Mentoring activities were carried out on August 13-16, 2024. Activities were carried out in the form of counseling and training in preparing financial reports. The results of mentoring activities are in the form of an understanding of preparing financial reports that have met the standards. From these activities, it is hoped that it can increase knowledge and learning for UMKM actors as well as accuracy in decision making